2019
DOI: 10.1002/jnr.24535
|View full text |Cite
|
Sign up to set email alerts
|

Greater neurodegeneration and behavioral deficits after single closed head traumatic brain injury in adolescent versus adult male mice

Abstract: Traumatic brain injury (TBI) is a major public health concern affecting 2.8 million people per year in the United States, of whom about 1 million are children under 19 years old. Animal models of TBI have been developed and used in multiple ages of animals, but direct comparisons of adult and adolescent populations are rare. The current studies were undertaken to directly compare outcomes between adult and adolescent male mice, using a closed head, single‐impact model of TBI. Six‐week‐old adolescent and 9‐week… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Both animal and human studies of TON are typically conducted in adult populations (e.g., due to higher incidence in military personnel). As we and others have previously shown that outcome differences between mice separated by as little as two weeks of age arise after mild TBI in memory performance, mortality, and severity of brain pathophysiology [26][27][28][29][30][31][32] it is, therefore, likely that these differences are also present across age groups in the visual system. Moreover, studies on optic nerve injury have only recently begun to analyze central projections of the optic nerve like the LGN [17,21,33,34], the SC [21,23], and the supra-oculomotor nucleus and caudate [21] but none have been conducted in an adolescent population.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Both animal and human studies of TON are typically conducted in adult populations (e.g., due to higher incidence in military personnel). As we and others have previously shown that outcome differences between mice separated by as little as two weeks of age arise after mild TBI in memory performance, mortality, and severity of brain pathophysiology [26][27][28][29][30][31][32] it is, therefore, likely that these differences are also present across age groups in the visual system. Moreover, studies on optic nerve injury have only recently begun to analyze central projections of the optic nerve like the LGN [17,21,33,34], the SC [21,23], and the supra-oculomotor nucleus and caudate [21] but none have been conducted in an adolescent population.…”
Section: Introductionmentioning
confidence: 77%
“…We have previously reported degeneration in the optic tract, lateral geniculate nucleus, and superior colliculus within one week after TBI in adult male mice, but TON has not yet been studied in an adolescent population. [24] [26][27][28][29][30][31][32]In the current studies we expand our previous findings in adolescent mice, and include measures of retinal ganglion cell loss, changes to visual acuity, and changes in subcortical targets of the optic nerve both one week and one month after injury.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…TBI is a significant public health concern affecting 2.8 million people per year in the United States. 1 "TBI is defined as an alteration in brain function, or other evidence of brain pathology, caused by an external force (for example, falls, assaults, motor vehicle accidents, sports injuries). Non-TBI (acquired brain injury) is due to internal factors such as stroke, pressure from a tumor, lack of oxygen (heart attack), infections such meningitis, seizure, neurotoxins, encephalitis, and drugs (Brain Injury Association, Fairfax, VA)."…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammatory response and neuroinflammation are critical events in the pathogenesis of traumatic brain injury (TBI). TBI is a significant public health concern affecting 2.8 million people per year in the United States 1 . “TBI is defined as an alteration in brain function, or other evidence of brain pathology, caused by an external force (for example, falls, assaults, motor vehicle accidents, sports injuries).…”
Section: Introductionmentioning
confidence: 99%